Business plan for a starting NGO supporting patients suffering from Myalgic encephalomyelitis/ Chronic Fatigue Syndrome (ME/CFS) in the Czech Republic - Homolka, Petr (2021)
In this thesis, the key guidelines for the process of strategic planning for a nonprofit organisations are outlined. Furthermore, the most important scientific findings regarding ME/CFS are described. The theoretical frameworks and process are then used to develop a 3-year strategic plan for Neunavni Foundation, a new Czech nonprofit organisation which aspires to support and improve the situation of ME/CFS patients in the Czech Republic. During the process, the needs of the beneficiaries and external trends are mapped, and the outcomes used to develop the mission and vision statements as well as define the key areas of activities. Moreover, the theory of change is developed, and the feasibility of the entire strategy is analysed. In the last part, tactical plan for the first year of the strategic plan is prepared.